Jack of Cape Grim : a Victorian adventure - Roberts, J. P. (Janine P.) (Richmond, Vic. : Greenhouse, 1986)
Detailed account of organised and armed attacks on settlers in the Western Port District by five Tasmanian Aborigines brought to Victoria by G.A. Robinson - Truganini, Matilda (Pyterrunner), Fanny (Planobeena), Jack (Tunnerminnerwait/Napoleon) and Robert Smallboy (Peevay); contact history and Aboriginal resistance in Tasmania and Victoria; work of Chief Protector and Assistant Protectors of Aborigines; capture, trial and execution of Aboriginal guerrillas.
Includes index.
Bibliography: p. [108]-117.
Keywords: Truganini, -- approximately 1812-1876.; Aboriginal Tasmanians -- Treatment; Aboriginal Tasmanians -- Victoria -- Treatment; Aboriginal Tasmanians -- Government relations; Aboriginal Australians -- Victoria -- Government relations; Literature and stories - Non indigenous - Fiction; Settlement and contacts; Race relations - Violent - Massacres, murders, poisonings etc. - To 1900.; Victoria -- History -- 1834-1851.; Western Port (Vic SJ55-09); Melbourne (Vic SJ55-05); Tasmania (Tas)